Age, sexuality and hegemonic masculinity: Exploring older gay men's masculinity practices at work. Issue 6 (4th June 2020) - Ozturk, Mustafa Bilgehan; Rumens, Nick; Tatli, Ahu
Abstract : This article examines how older gay men practice masculinity in heteronormative organizational settings. Our analysis of in‐depth interview data yields two key masculinity practices: maintaining heteronormativity and embodying change. Older gay men's masculinity practices that conform to the ideals of hegemonic masculinity have the effect of maintaining heteronormativity. Embodying change refers to older gay men's masculinity practices that leverage accumulated life experiences to negotiate heteronormativity for change, although such agency is constrained by individuals' material and symbolic commitments to heteronormativity. By delineating these two clusters of practices and exploring the dynamic relationality between individual action and organizational order from a practice‐based perspective, we extend the conceptual scope of hegemonic masculinity. Furthermore, by investigating how older gay men navigate ageing and sexuality in organizations, we show the constraining and enabling effects of ageing as a social and embodied process on gay men's masculinity practices.